The official as an expert. Professionalism and diletantism in the public function of the Generalitat of Catalonia (1931-‍1939) - Martínez Fiol, David (Historia y Política, 2019)
The Spain of the first half of the twentieth century operated an intense process of political and economic modernization which resulted in the growth of urban areas and the services sector. This phenomenon facilitated the expansion of a new middle class with university studies chose as a means of economic survival and social promotion, offer their services to the different public administrations existing in Spain. In the case of Catalonia, the realization of the Mancomunitat first in 1914-‍1924 and in 1931-‍1939 the Generalitat then opened a window job opportunities to these middle classes of university education. However, in the construction of the Republican Generalitat, not always academic merit and professional it was the prerequisite for the recruitment of officials. The struggle against the monarchy of Alfonso XIII and the regime primoriverista served for some sectors of the Catalan political space as a letter of presentation sufficient to obtain public employment. This article analyzes how were built in Catalonia in the thirties, different discourses on how it should be genuine public administration professional in the Catalonian self-goverment.